Avaliação de múltiplos mecanismos de resistência associados em isolados clínicos de Klebsiella pneumoniae resistente aos carbapenêmicos - Dalmolin, Tanise Vendruscolo (2015)
Antimicrobial resistance is considered a serious public health problem worldwide and complicates the treatment of infections caused by resistant microorganisms. The carbapenems are antimicrobial agents considered the last resource for treatment of severe infections caused by Klebsiella pneumoniae and the resistance to β-lactams can result in the accumulation of different resistance mechanisms (carbapenemases, efflux pump and loss of porins). This study aimed to evaluate multiple resistance mechanisms in 27 clinical isolates of K. pneumoniae resistant to carbapenems coming from the University Hospital of Santa Maria-RS from July 2013 to August 2014. These isolates were evaluated the susceptibility profiles through broth microdilution against ciprofloxacin, imipenem, ertapenem, meropenem, cefepime, ceftazidime and cefoxitin. Carbapenemase detection was performed through phenotypic tests with combined disc test with phenylboronic acid (AFB) and ethylenediaminetetraacetic acid (EDTA) and Blue-Carba test. In addition, genotypic tests to detect genes enconding carbapenemase were performed. Efflux pump was evaluated by broth microdilution together with efflux pump inhibitor and loss of porins were evaluated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). High levels of resistance verified by the minimum inhibitory concentration (MIC) 50 and 90 for ciprofloxacin (64 and 128μg/mL), imipenem (32 to >128μg/mL), ertapenem (>128 and >128μg/mL), meropenem (128 and >128 μg/mL), cefepime (>128 and >128 μg/mL), ceftazidime (64 and 128μg/mL) and cefoxitin (128 and >128 μg/mL), respectively. In the resistance through carbapenemases production, 89% of the clinical isolates showed blaKPC gene and no clinical isolated showed genes encoding the metallo- β-lactamases. It was observed that the Blue-Carba test and combined disc test with AFB showed 100% concordance, while the combined disc test with EDTA showed high number of false positive (48%) when compared with genotypic test. Four isolates showed phenotypic profile consistent with the presence of efflux pump and all clinical isolates had lost one or both porins, being that in three isolated, this was the only resistance mechanism found. In 14% of the isolates can observe simultaneously observe the presence of three resistance mechanisms. Consequently, it is of fundamental scientific interest that studies are conducted in order to investigate and understand the mechanisms involved in resistance to carbapenems in order to assist strategies of prevention and infection control.